A Case of Malignant Melanoma of the Uterine Cervix with Disseminated Metastases throughout the Vaginal Wall. (18th January 2017) - Noguchi, Tomoko; Ota, Nami; Mabuchi, Yasushi; Yagi, Shigetaka; Minami, Sawako; Okuhira, Hisako; Yamamoto, Yuki; Nakamura, Yasushi; Ino, Kazuhiko
Abstract : Malignant melanoma (MM) in the female genital tract accounts for less than 2% of all melanomas, and the vast majority associated occur in the vulva and vagina. Primary MM of the uterine cervix is extremely rare and its prognosis is very poor. We report a case of primary MM of the cervix with dissemination throughout the vaginal wall. A 66-year-old woman presented with postmenopausal bleeding. Gynecologic examination demonstrated a 2 cm polypoid blackish-pigmented tumor on the cervix with multiple small blackish-pigmented lesions throughout the vaginal wall. Cervical Pap smear cytology showed malignant melanoma. MRI and PET/CT did not detect any distant or lymph node metastases. She underwent radical hysterectomy, pelvic lymphadenectomy, and total vaginectomy. The pathological diagnosis was FIGO stage IIIA primary cervical MM. She received adjuvant chemotherapy with 6 courses of dacarbazine, but 6 months later, multiple lung metastases were detected. Despite 4 courses of anti-PD-1 antibody (nivolumab) treatment, she died of the disease 13 months after surgery.